Intellectual Disability and Psychiatric Diagnoses of Children and Adolescents with a History of Stressful Events and Social Deprivation in Brazil: Preliminary Results. IQ, Depression and Stress - Oliveira, Paula Approbato de; Moreira, Carolina Fuentes; Scivoletto, Sandra; Rocca, Cristiana Castanho de Almeida; Fuentes, Daniel; Cunha, Paulo Jannuzzi (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Background: Studies have shown that stressful events in childhood are associated with impairments in cognitive functions and intellectual disability. Objective: Compare the intellectual functioning in groups of Brazilian children and adolescents with a history of stressful events with lifetime history of depression and without lifetime history of depression. Method: 30 children and adolescents underwent psychiatric evaluation and neuropsychological assessment of estimated intellectual quotient (EIQ), verbal knowledge, and visuospatial skills. Results: 15 patients (50%) had EIQ within the average and 6 had EIQ in the lower average (20%) for Brazilian standardized norms. The other part had at least some degree of intellectual disability and they were classified as: 2 mild mental retardation (6.7%) and 7 borderline (23.3%). Also, half of the sample had at least one lifetime depressive episode, and the performance in EIQ and visuospatial skills was worse in this group. Conclusion: 50% of the children and adolescents with a history of early stressful events and social deprivation had at least some degree of intellectual disability. In addition, a subgroup with history of depressive episodes had worse EIQ performance when compared to those without depression, possibly due to a greater impairment in visuospatial skills. The specific role of impaired right cerebral hemisphere, corpus callosum, and prefrontal cortex associated with depressive disorders and maltreatment should be investigated in further studies.